PENERAPAN MODEL DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PAI DI SMP NEGERI 4 LHOKSEUMAWE - TARMIZI TARMIZI (STRATEGY : Jurnal Inovasi Strategi dan Model Pembelajaran, 2022)
One of the reasons for the low learning outcomes of students in Islamic Religious Education (PAI) is that the learning model used by the teacher is not appropriate, the teacher carries out learning with a conventional one-way model, only transferring information from the teacher to students. Such a strategy makes students quickly bored and boring. Therefore, teachers need to apply appropriate learning models to be able to stimulate students to learn actively, creatively and innovatively, so as to improve their learning outcomes. This study was designed to conduct research on the use of discovery learning models in improving student learning outcomes on the material "Faith in Allah SWT". The research subjects were seventh grade students of SMP Negeri 4 Lhokseumawe with 32 students. The results show that the application of the discovery learning model can stimulate the learning process in the classroom, where students can contribute actively, critically, and innovatively, so that PAI learning outcomes can increase. It can be seen from the implementation of the first cycle that there has been an increase in learning outcomes compared to the pre-cycle results, because the scores in the first cycle obtained 12 people >70 (according to the KKM) with a percentage of 35.29%. Furthermore, the results of observer observations on teacher activities in the first cycle reached 81.72% and observer observations on student activities reached 80.76%. While the implementation of the second cycle experienced a significant increase, namely 32 students completed with a percentage of 94.11%, with observations on teacher activities reaching 95.19% and observations on student activities reaching 96.15%. ABSTRAKRendahnya hasil belajar peserta didik pada pembelajaran Pendidikan Agama Islam (PAI) salah satunnya disebabkan model pembelajaran yang digunakan guru belum tepat, guru melaksanakan pembelajaran dengan model konvensional yang bersifat satu arah, hanya mentranfer informasi dari guru ke peserta didik. Strategi semacam itu membuat peserta didik cepat jenuh dan membosankan. Oleh karena itu guru perlu menerapkan model pembelajaran yang tepat agar mampu merangsang peserta didik untuk belajar aktif, kreatif dan inovatif, sehingga dapat meningkatkan hasil belajarnya. Penelitian ini didesain untuk melakukan penelitian terhadap penggunaan model discovery learning dalam meningkatkan hasil belajar siswa pada materi “Iman kepada Allah SWT”. Subjek penelitian adalah peserta didik kelas VII SMP Negeri 4 Lhokseumawe dengan jumlah siswa 32 orang. Hasil penelitian menunjukkan bahwa penerapan model discovery learning dapat membangkitkan proses pembelajaran di dalam kelas, di mana peserta didik dapat berkonstribusi secara aktif, kritis, dan inovatif, sehingga hasil belajar PAI dapat meningkat. Hal tersebut terlihat dari pelaksanaan siklus I sudah mulai ada peningkatan hasil belajar dibandingkan hasil pra-siklus, karena perolehan nilai pada siklus I memperoleh 12 orang >70 (sesuai KKM) dengan persentase 35,29%. Selanjutnya hasil observasi pengamat terhadap kegiatan guru pada siklus I mencapai 81,72% dan observasi pengamat pada kegiatan siswa mencapai 80,76%. Sedangkan Pelaksanaan siklus II mengalami peningkatan secara signifikan, yaitu 32 orang siswa tuntas dengan persentase 94,11%, dengan hasil pengamatan terhadap kegiatan guru mencapai 95,19% dan hasil pengamatan terhadap kegiatan siswa mencapai 96,15%.